2004
DOI: 10.1111/j.1532-5415.2004.52355.x
|View full text |Cite
|
Sign up to set email alerts
|

The Health Status of Elderly Veteran Enrollees in the Veterans Health Administration

Abstract: Elderly veteran enrollees have substantial disease burden, as reflected by major impairments across multiple dimensions of HRQoL. These findings bear important implications for use of services, suggesting that the Veterans Health Administration will require considerable resources to provide care for its aging population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 16 publications
6
89
1
Order By: Relevance
“…In particular, aspects of mental health did not appear to decline with increasing age, as seen with the VR-36 MCS (p = 0.10). A decline in physical function with increasing age, without a corresponding decline in mental health, corresponds with what might be expected, based on previous work (Selim et al, 2004). HRQoL scores varied by the respondent's sex (Table 3.7).…”
Section: Chapter Three Analytic Methods and Results: Validation Of Isupporting
confidence: 83%
“…In particular, aspects of mental health did not appear to decline with increasing age, as seen with the VR-36 MCS (p = 0.10). A decline in physical function with increasing age, without a corresponding decline in mental health, corresponds with what might be expected, based on previous work (Selim et al, 2004). HRQoL scores varied by the respondent's sex (Table 3.7).…”
Section: Chapter Three Analytic Methods and Results: Validation Of Isupporting
confidence: 83%
“…Even fewer older adults met these guidelines; among older adults aged 65 to 74, only 16 percent met the guidelines for moderate-intensity exercise and 13 percent met the guidelines for vigorous-intensity exercise [2]. Although U.S. veterans are more physically active than nonveterans across all age groups, many veterans also do not meet Federal recommendations for weekly moderate physical activity [3][4]. In an analysis of a national sample of veterans, Littman et al found that 45.6 percent of veterans aged 50 to 59 and 40.7 percent of veterans 70 years met daily physical activity level recommendations [4].…”
Section: Introductionmentioning
confidence: 99%
“…In initial studies comparing VA and non-VA patients after acute myocardial infarction (AMI), veterans were shown to have more comorbidities, worse overall health status, and lower socioeconomic status than non-veterans. [24][25][26][27][28] Veterans were also reported as having a higher one-year mortality rate after AMI than non-veterans, [27][28] and were less likely to receive coronary angiography. 26 To address these reported disparities in the quality of cardiovascular care received by veterans and provide a mechanism by which the Congressional mandate could be met, the VA introduced a multi-layered plan to improve cardiovascular care by opening new catheterization labs, adopting national VA performance measures, and developing a national quality improvement program for cardiac catheterization procedures.…”
Section: Background Health It Implementation In the United Statesmentioning
confidence: 99%